Attitudes, knowledge and treatment of low back pain amongst nurses in the Eastern Cape, South Africa - Liezel Cilliers; Soraya Maart (AOSIS, 2013)
Background: One of the high-risk professions for the development of musculoskeletal problems is nursing. Studies have reported that there is a high prevalence of low back pain (LBP) amongst South African nurses, but very little is known regarding the prevention and self-treatment principles for LBP in this group. Objectives: The objective of this study is to evaluate the knowledge, attitudes and beliefs about the prevention and self-treatment principles for LBP amongst nursing staff in Cecilia Makiwane Hospital, Eastern Cape. Methods: The study population consisted of all qualified nurses employed at the hospital. A cross-sectional survey with a purposive convenience sampling method was used. A questionnaire was designed using literature from established sources. The questionnaire was distributed manually and data obtained were analysed using EPI-INFO4. Results: The study found that the majority of the participants experienced LBP on a regular basis. The participants could identify the most important physical risk factors associated with the development of LBP, but neglected the psychological risk factors. Action taken after the development of LBP included professional consultations as well as medication and bed rest.The participants identified the different components of a preventative exercise programme but only focused on the physical and not psychological components associated with LBP. Conclusions: LBP is a serious problem amongst the nurses at the hospital, but no proactiveapproach is taken in order to address this problem. Policy guidelines and a comprehensive prevention and treatment programme need to be designed and implemented to address this issue.